Antigypsyism and Film / Antiziganismus und Film - Mladenova, Radmila; Tobias von Borcke; Brunssen, Pavel; Markus End; Anja Reuss (Heidelberg University Publishing (heiUP), 2020)
Antiziganism is a common phenomenon on the big screen. To examine this issue from various perspectives, acclaimed scholars and junior researchers, filmmakers and human rights activists, both Roma and non-Roma, gathered in Berlin in 2018 and presented their research output, shared personal testimonies and discussed films at the international conference "Antigypsyism and Film". The present bilingual volume is a documentation of the conference proceedings. It contains academic articles and essays as well as interviews with filmmakers grouped in four thematic sections: antigypsyism in film, the question of ethics, strategies of subversion and antigypsyism in comparison to other forms of racism.; Antiziganismus ist Normalität auf der großen Leinwand. Um dieses Problem aus unterschiedlichen Perspektiven zu untersuchen, versammelten sich Wissenschaftler und Nachwuchsforscher, Filmemacher und Menschenrechtsaktivisten - Roma wie Nicht-Roma - 2018 in Berlin zu einer internationalen Tagung: "Antiziganismus und Film". Sie präsentierten ihre Forschungsergebnisse, teilten persönliche Zeugnisse und diskutierten Filme. Der vorliegende zweisprachige Band dokumentiert diese in ihrer Form bisher einzigartige Tagung. Der Tagungsband umfasst wissenschaftliche Artikel und Essays sowie Interviews mit Filmemachern, unterteilt in vier thematische Abschnitte: Antiziganismus im Film, Fragen der Ethik, Strategien der Subversion und Antiziganismus im Verhältnis zu anderen Ressentiments.